Clinicians’ Attitudes Toward Therapeutic Alliance in ETherapy - Madalina, Sucala (2013)
Although therapeutic alliance is a crucial factor in face-to-face therapies, no data exist on clinicians’ attitudes towards alliance in E-therapy. The study explored clinicians’ perceived importance of alliance in E-therapy, clinicians’ confidence in their skills to develop alliance in E-therapy, and whether attitudes towards alliance in E-therapy are associated with intended E-therapy practice. Clinicians (n=106) responded to an online survey. The majority of clinicians considered alliance to be extremely important in both face-to-face therapy and E-therapy. However, clinicians’ ratings of the importance of alliance in face-to-face therapies were significantly higher than their ratings of the importance of alliance in E-therapy. Clinicians reported less confidence in their skills to develop alliance in E-therapy than in face-to-face therapy. Intended E-therapy practice correlated with confidence in one’s ability to develop alliance in E-therapy and with previous E-therapy practice.